Pengembangan Interface Audit Kualitatif untuk Mendukung KLPCM RME di Rumah Sakit Umum Daerah X - Fita Rusdian Ikawati; Untung Slamet Suhariyono; Ryan Dwi Saputra; Saepul Muslim; Margareta, Ananda Agustin; Arnoldus Anugerah Agung; Jazilatul Maghfiroh; Tirta Hadi Santoso; Akbar Novando Putra Wahandika; Sheyla Nur Afni (Gayaku Publisher, 2025)
Qualitative audits are a crucial component in evaluating the quality of healthcare services through the KLPCM system. However, at Regional General Hospital X, the audit process is still performed manually using spreadsheets, which leads to inefficiencies and a high risk of errors. This community service project aimed to design a digital interface for qualitative audits to enhance the effectiveness of audit activities and support integration with Electronic Medical Records (EMR). The method used was Participatory Action Research (PAR), involving observation, interviews, and the collaborative design and validation of a prototype with audit staff and field supervisors. The results showed that the proposed interface design reduced administrative workload, improved data accuracy, and expedited reporting processes. The prototype received positive responses from users and is expected to serve as an initial step toward the digital transformation of hospital quality audit systems